2016
DOI: 10.3390/en9070556
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study of the Effects of Interbeds on Hydraulic Fracture Propagation in Shale Formation

Abstract: Abstract:To investigate how the characteristics of interbeds affect hydraulic fracture propagation in the continental shale formation, a series of 300 mmˆ300 mmˆ300 mm concrete blocks with varying interbeds, based on outcrop observation and core measurement of Chang 7-2 shale formation, were prepared to conduct the hydraulic fracturing experiments. The results reveal that the breakdown pressure increases with the rise of thickness and strength of interbeds under the same in-situ field stress and injection rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Raman spectroscopy is a fast and nondestructive equipment to create the profile of maturity, S1, S2, and PI, and accelerate the analysis with good precision. Moreover, it has been shown that organic matter has a non-negligible effect on hydraulic fracturing of organic rich unconventional reservoirs [91][92][93][94][95][96][97][98], therefore such fast methods to characterize organic matter can be useful in the geomechanical simulation of hydraulic fracturing operations.…”
Section: Pi = S1mentioning
confidence: 99%
“…Raman spectroscopy is a fast and nondestructive equipment to create the profile of maturity, S1, S2, and PI, and accelerate the analysis with good precision. Moreover, it has been shown that organic matter has a non-negligible effect on hydraulic fracturing of organic rich unconventional reservoirs [91][92][93][94][95][96][97][98], therefore such fast methods to characterize organic matter can be useful in the geomechanical simulation of hydraulic fracturing operations.…”
Section: Pi = S1mentioning
confidence: 99%
“…Since then, this technique as one of the Enhanced Oil Recovery (EOR), is conducted into the wellbore of conventional reservoir and it increases the production and wellbore lifetime. Furthermore, it has made a significant contribution to the development of unconventional reservoirs (Guo et al, 2014;Montgomery & Smith, 2010;Zhao et al, 2016). In addition to stimulating oil and gas production and enhanced geothermal energy, this method is also used for determining the magnitudes and directions of in-situ stresses in the mining and civil engineering underground projects (Pine et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the impact of bedding planes on propagation, Grasselli et al conducted a research on the problem of crack initiation. Zhao et al studied the effect of the thickness and strength of bedding planes on the fracture propagation. Men et al found out that, with the increase in the bedding plane angles, the maximum principal stress and bedding planes dominantly control the initiation and propagation of the fracture crack.…”
Section: Introductionmentioning
confidence: 99%